An assessment of the backyard livestock and poultry raising as potential vaible alternative livelihood activities in selected barangays in Carles, Iloilo - Flamiano, Emelda B.
The study conducted to assess backyard livestock and poultry raising as potential viable alternative livelihood activities in fifteen barangays of Carles, Iloilo. The descriptive method of research was used and data were collected through personal interview using structured survey questionnaire. A total of 98 households were dtermined as the sample size using the Slovin's Formula with 10 percent margin of error. The respondents were identified through systematic sampling. The respondents kept on backyard raising primarily for financial assistance to household basic needs, for emergency need that arises, to dress/laughter anytime for home consumption and for special occasion, to support student expenses, to add/source of income, to serve as piggy bank and to utilize kitchen waste. The average backyard livestock production per respondent was three heads per month, and nine heads per respondent for backyard poultry production. The backyard livestock raising can contribute an average income of â‚±1,076.00 per month, as accounted from an average disposition of three heads either sold alive or slaughtered for household consumption with an average percent contribution to total household income of twenty-five percent. Whereas, backyard poultry raising has an average of four heads disposed per month either sold alive/dressed for household consumption and accounted for an average income of â‚±174.00 per month with five percent average contribution to total household income. Based on the findings, the following conclusions were drawn: 1) Backyard livestock and poultry raising are potentially viable alternative livelihood activities in selected barangays of Carles. 2) A great majority of the respondents (83%) is engaged in backyard raising particularly in poultry in spite of the outbreak of diseases and high cost of feeds/stocks they encountered in raising backyard livestock and poultry. 3) About one third of the respondents (35%) responded that they engaged in backyard raising for financial assistance; and more than ten percent (16%) responded for emergency need that arises. Based on the following conclusions of the study, the following are recommended: 1) The government should have an ongoing assistance to prevent animals from diseases as in fowl/hog cholera. 2)animal raisers should utilize locally produced feeds as an alternative for the high cost of animal feeds. 3) a similar study should be conducted in a different settling and on a wider scale.